The fabrication and evaluation of on-chip gas pressure sensors - Masuri Othman (1990)
In this paper we describe the fabrication and evaluation of on-chip silicon-based gas pressure sensors. The sensor is fabricated using standard Integrated Circuit (IC) fabrication technology except the final etching to delineate cantilever beams. The beam which is the key element in the sensor system is driven to its resonant frequency by the difference in thermal expansion between silicon and oxide. The output detection is done by utilising the piezoresistive effect in a polysilicon resistor defined on top of the oxide layer. It is found that the resonant frequency (fR)) varies linearly with the gas pressure from 100 mmHg to about 500 mmH, thus it is possible for system to be used as a gas pressure sensor